DAYA TAHAN HIDUP PSEUDOMONAD FLUORESEN DI DALAM MATRIKS ORGANIK PILEN TEMBAKAU SURVIVAL OF FLUORESCENT PSEUDOMONAD IN ORGANIC MATRIX OF COATED TOBACCO-SEED - Arwiyanto, Triwidodo (Pembangunan Pedesaan, 2007)
Strain Pf-20 of Pseudomonas putida and pseudomonad fluoresent isolate Pf- 33 are the biological control agents of tobacco bacterial wilt caused by Ralstonia solanacearum. The method of delivery of the biological control, however, is inefficient and laborious due to the need a lot of bacterial suspension for ipping the seedlings before transplanting. The use of cattle manure as a main substance for coating of tobacco seed was reported here. The cattle manure was sieved to 0.09 mm then mixed with 0.1% CMC and suspension of Pf-20 and Pf-33. Prior coating, the seeds were surface sterilized with 1% sodium hypochloride for 30 seconds then air dried. The sterilized seeds were coated with the matrix until the size is 1.5- 2.00 mm. The results indicated that fluorescent pseudomonad could survive longer in the coated seed when strain Pf-20 of P. putida and fluorescent pseudomonad isolate Pf-33 were used together in one formulation. Fluorescent pseudomonad could survive in the coated seed for 4 weeks. Seed germination, however, was not affected by coating with the materials stated above.